Caracterização da gramínea vetiveria zizanioides para aplicação na recuperação de áreas degradadas por erosão - Margarita Maria Duenas Orozco (2009)
The appearance of degraded areas in Brazil has been increasing considerably along the years, causing countless damages to the environment. According to FAO (2005), approximately 16% of the total area of Brazil presents some state of soil degradation induced by human activities. In reason of this, the present study has as objective characterizes the Vetiver grass (Vetiveria zizanioides) for application in the recovery of areas degraded by erosion, through the installation of plots in field and accomplishment of a laboratory and field experimental program. This grass was chosen because of its special characteristics, especially the high tolerance to extreme conditions, little height and extensive root system. To reach the objective, it was considered the adaptation and growth of the plant in the studied substrata, analyzed in physical and chemical level. Besides, the mechanical properties of the Vetiveria zizanioides roots were evaluated, studying the increase in resistance imposed by roots in the soil, as well as its root tensile strength. In the same way, it was considered the soil losses generated by the water erosion in each plot with different implanted treatment. The results showed that the grass requires care in its initial growth phase as well as other plants; however, it is resistant and can survive under adverse conditions. Concerning shear strength, unlike the expected, the soil-root system presented smaller resistances than the soil without roots. Possibly the choice of the work scale was not the most appropriate, being recommended working with larger samples or to do the tests directly in field with larger size equipments. Confirming results reported by other authors, great variability was observed in the data regarding the root tensile strength. In the same way, it was ratified the trend of smaller diameters roots to present larger tensile strength. Regarding the soil losses, it was observed that the largest losses were generated in the control plots, where there was no type of soil cover, as well as in the area of larger inclination and larger spacing among the strings of the grass. In face of those results, it is verified that is not possible to assure the success of bioengineering techniques application in the recovery of degraded areas just with isolated studies. The interest on the subject is not exhausted with this research, so it is necessary to carry out additional researches on real scale.